Reproductive safety evaluation of L-Ergothioneine. (June 2015) - Forster, Roy; Spézia, François; Papineau, Dominique; Sabadie, Caroline; Erdelmeier, Irene; Moutet, Marc; Yadan, Jean-Claude
Highlights: L-Ergothioneine is synthesized by bacteria and fungi and is present in many human foodstuffs. We investigated the potential reproductive toxicity of nature-identical L-Ergothioneine in rats by dietary administration. No effects on reproductive parameters in F0 rats after >10 weeks administration at 600-700 mg/kg/day L-Ergothioneine. Parameters evaluated included: mating, gestation, pre/post-implantation loss and pup data (number, weight, sex viability). Abstract: L-Ergothioneine is a naturally occurring histidine-derived betaine (CAS No: 497-30-3) synthesized by bacteria and fungi, and found ubiquitously in plants and animals. It is present in many human foodstuffs. We evaluated the potential reproductive toxicity of L-Ergothioneine in Sprague-Dawley rats. L-Ergothioneine was administered at concentrations of 0.1, 0.3 or 0.9% in diet to F0 males (for 10 weeks before pairing and 3 weeks during pairing) and F0 females (for 13 weeks before pairing, during pairing and gestation, and until day 5 of lactation). Systemic exposure increased with dose-level, but not dose proportionally, suggesting saturation of uptake mechanisms. No clinical signs of toxicity were observed and there were no effects of L-Ergothioneine treatment on mating and reproductive performance or parameters of fertility. All animals mated within a similar number of days and pregnancy rates were uniformly high in control and treated groups. There were no effects of treatment with L-Ergothioneine on the duration of gestation, pre- and post-implantation losses, number of pups delivered and viability index, or on litter parameters (litter size, clinical signs, body weight or sex ratio) and the repartition of found dead/cannibalized pups. In conclusion, L-Ergothioneine was well tolerated and without adverse effects on the reproductive parameters evaluated.